2021
DOI: 10.1007/s10010-021-00513-7
|View full text |Cite|
|
Sign up to set email alerts
|

Operating behavior and performance of oil-lubricated plastic gears

Abstract: Plastic gears and their numerous applications have become an integral part of industrial practice. In particular, the ability to produce large numbers of gears cost-effectively using injection molding techniques is making a significant contribution to growing market shares. Compared to conventional steel materials, however, the material properties of thermoplastics differ fundamentally. In particular, the high temperature dependence of the material properties and the lower strength pose challenges for designer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additionally, reinforcement such as glass/carbon fiber in gear materials has also been observed in gear performance investigation. [15][16][17] Whereas, in additive manufacturing process, due to limitation of reinforcement not many varieties of material have been used in polymer gears for its experimental investigation. PA618, PLA, ABS and nano clay ABS are only few materials which have been used so far for producing gears using additive manufacturing through FDM (Fused Deposition Modelling) method for gear pair performance investigation.…”
Section: Types Of Manufacturingmentioning
confidence: 99%
“…Additionally, reinforcement such as glass/carbon fiber in gear materials has also been observed in gear performance investigation. [15][16][17] Whereas, in additive manufacturing process, due to limitation of reinforcement not many varieties of material have been used in polymer gears for its experimental investigation. PA618, PLA, ABS and nano clay ABS are only few materials which have been used so far for producing gears using additive manufacturing through FDM (Fused Deposition Modelling) method for gear pair performance investigation.…”
Section: Types Of Manufacturingmentioning
confidence: 99%
“…It can be said that CFPEEK gear shows good root load carrying capacity with poor tooth flank load carrying capacity. 157 Using numerical method, it has been found that coating material with large value of Young’s modulus and coating layer thickness decreases tooth tip deflection which further reduce wear process. 158 However, the friction coefficient found unaffected at a value above 5 mm of radii of relative curvature under dry film lubrication when tested for acetal gear pair.…”
Section: Classification Of Review Of Polymer Gearingmentioning
confidence: 99%